2006
DOI: 10.1038/sj.emboj.7601422
|View full text |Cite
|
Sign up to set email alerts
|

The contact system—a novel branch of innate immunity generating antibacterial peptides

Abstract: Activation of the contact system has two classical consequences: initiation of the intrinsic pathway of coagulation, and cleavage of high molecular weight kininogen (HK) leading to the release of bradykinin, a potent proinflammatory peptide. In human plasma, activation of the contact system at the surface of significant bacterial pathogens was found to result in further HK processing and bacterial killing. A fragment comprising the D3 domain of HK is generated, and within this fragment a sequence of 26 amino a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
149
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 134 publications
(152 citation statements)
references
References 55 publications
3
149
0
Order By: Relevance
“…2B). These results were similar to the bacterial destruction caused by membrane-acting antimicrobial peptides (12,14,15,22). Correspondingly, studies using the impermeant fluorescent probe FITC demonstrated that only HCIIa caused membrane permeabilization of bacterial cells (Fig.…”
Section: Cleaved Hcii Is Antimicrobialsupporting
confidence: 67%
See 1 more Smart Citation
“…2B). These results were similar to the bacterial destruction caused by membrane-acting antimicrobial peptides (12,14,15,22). Correspondingly, studies using the impermeant fluorescent probe FITC demonstrated that only HCIIa caused membrane permeabilization of bacterial cells (Fig.…”
Section: Cleaved Hcii Is Antimicrobialsupporting
confidence: 67%
“…For instance, although ATIII levels are reduced in almost all conditions associated with disseminated intravascular coagulation, reduced plasma levels of HCII are primarily detected during infection (8)(9)(10)(11). Increasing evidence pointing toward a close link between hemostasis, proteolysis, and host defense (12)(13)(14)(15)(16)(17) raised the hypothesis that HCII could play a role in host defense against infections.…”
mentioning
confidence: 99%
“…Complement has been shown to potentiate the coagulation cascade by inhibiting fibrinolysis, through C5a, which induces the expression of tissue factor and plasminogen-activator inhibitor 1 (37), whereas proteases of the coagulation and fibrinolytic system were shown to cleave and activate C3 and JULY 24, 2015 • VOLUME 290 • NUMBER 30 generate C5a (21,38). Additionally, during infections, localized complement-mediated coagulation activation enhances clotting, which not only provides a mechanical barrier against the spread of invading bacteria, but also helps in generating antimicrobial peptides and support the inflammatory response (21,39).…”
Section: Discussionmentioning
confidence: 99%
“…The pH was raised to 7.0 with 1 M Tris solution. Production of rabbit antibodies against a peptide of high-molecular-mass kininogen (NAT26) has been described (Frick et al, 2006).…”
Section: Methodsmentioning
confidence: 99%